Modelling the Effect of Nanoscale Zero-Valent Iron (nZVI), Biochar (BC) and Nanoscale Zero-Valent Iron/Biochar (nZVI/BC) on the Adsorption/Reduction of Nitrobenzene (NB) (Journal of Environmental Bioremediation and Toxicology, 2020)
In most instances, there exists an inaccuracy in interpretation of adsorption/reduction of substances using linear technique as it can only provide an approximate value of the measured parameter; the specific adsorption rate. This paper provides for the first-time modelling of the effect of nZVI/BC, nZVI and Biochar (BC) on the adsorption/reduction of nitrobenzene as modelled using Pseudo-1st order (PFO), Pseudo-2nd Order (PSO), Elovich and Avrami models. Pseudo-1st Order was the best model for nZVIBCg, whereas Pseudo-2nd Order was the best model for nZVI and BC on Nitrobenzene (NB) removal based on statistical dependencies that were used such as root-mean-squire error (RMSE), bias factor (BF), Akaike information criterion (AICc) and the adjusted coefficient of determination. Justifiably from the results, coupling nZVI and BC together will help in reducing more of NB than when individual compounds are used.
Keywords: nanoscale zero-valent iron; biochar; Pseudo-1st Order; Pseudo-2nd Order; nitrobenzene